Application of Modified Alvarado scoring system in the diagnosis of acute appendicitis: a study in a tertiary care hospital - Saha, Anup Kumar; Sandhu, Ankit; Vikram, Kumar (International Journal of Research in Medical Sciences, 2018)
Background: Acute Appendicitis is one of the common surgical diseases which require early intervention; however, it may lead to higher negative appendicectomy rates, in uncertain Diagnosis. Negative appendicectomy rate is 20-40%. There are various scoring systems to assist in diagnosis. The aim of this study is to assess the effectiveness of Modified Alvarado Scoring System (MASS) in patients with acute appendicitis in AGMC and GBP Hospital. Methods: This was a cross sectional study to evaluate the effectiveness of MASS in patients presenting with acute appendicitis. The Principal Investigator scored all the patients according to the variables of MASS and divided them into three groups. Group I included patients with MASS of four and below, Group II were patients with MASS of 5-6 and Group III included patients with MASS of seven and above. The diagnosis of acute appendicitis was confirmed by histopathological examination. Data was collected using a coded, pre-tested questionnaire and analyzed using SPSS statistical software version 11.5. Results: In this study, 36 cases out of 42 cases had acute appendicitis. The sensitivity of Modified Alvarado Score of >7 was 85.7% (proportion of true positive). The sensitivity was highest among males i.e., 92% while in females, it was 76.4%. Negative appendicectomy rates were highest among females (23.6%), whereas in case of males it was 8%. Conclusions: The present study has shown that MASS provides high degree of sensitivity, specificity, PPV, NPV and accuracy in the diagnosis of acute appendicitis and has found to be more helpful in and high positive predictive value for male patients as compared to females.